Mechanical Comparison of Four Different Types of Osteosynthesis in a 11-mm Advancement le Fort i Osteotomy - Lima, Valthierre Nunes de [UNESP]; Hadad, Henrique [UNESP]; Suguimoto, Roberto Macoto; Magro-Filho, Osvaldo [UNESP] (Wolters Kluwer, 2022)
Objective:This study aimed to evaluate 4 methods of osteosynthesis in the maxilla after a linear advance of 11 mm.Methodology:Le Fort I osteotomies were performed on 24 resin models and different osteosynthesis were applied in the anterior region. Group I received Lindorf plates; group II, modified Lindorf plates; group III, inverted T plates; and group IV, L plates. All groups received L plates in the posterior region. Analysis were performed through universal mechanical testing machine with an axial linear load until 5-mm displacement. The data obtained about the force and the amount of deformation were computed, thus the energy required for displacement and stiffness was calculated. Statistical analysis was performed using 2-way analysis (Shapiro-Wilk, followed by Holm-Sidak) (P < 0.05).Results:Groups I and II showed greater resistance to displacement (P < 0.05) than the other groups. The largest amount of maximum force exerted for the 5-mm displacement was in group II (91.73 N), followed by group I (87.46 N), presenting the best values in comparison with the other groups (P < 0.001). Group III had less stiffness (P < 0.001) than the other groups.Conclusions:The use of preclinical methodologies to verify the mechanical stability of fixation models allows a prediction in the choice of greater resistance systems. The fixation type with greater resistance to deformation was achieved with modified Linford plates followed by Linford plates in the anterior region and plate L bilaterally in the posterior region.
Keywords: Le Fort osteotomy; maxilla; orthognathic surgery